Onde está a Sífilis? Casuística do Hospital das Clínicas - Hyppólito, Luciane; Roselino, Ana Maria F. (Brazilian Journal of Sexually Transmitted Diseases, 1995)
The casuistic of acquired syphilis in the region of Ribeirão Preto, São Paulo State, Brazil, 1s presented. Seven hundred seventy three cases were diagnosed from 1979 to 1994. The decrease of number of cases in the last years, and the association with HIV/ ADIS in 30 cases are emphazised. An alert is rnade to the sanitarian authorities.